Evaluación del cambio porcentual del volumen intraventricular medido con 3D Slicer para discriminar complicaciones clínicas en pacientes pediátricos postoperados por hidrocefalia - Murrieta Ruiz, Andrea Valentina (2025)
Objective: To evaluate the percentage change in intraventricular volume, measured using 3D Slicer, as a tool to discriminate the presence of clinical complications in pediatric patients after hydrocephalus surgery at the Hospital Regional de Loreto. Methods: An observational analytical, retrospective study was conducted in 23 patients under 18 years of age who underwent ventriculoperitoneal shunt placement at the Hospital Regional de Loreto between January 2023 and July 2025, with baseline and postoperative serial computed tomography scans. Intraventricular volumes were segmented using 3D Slicer. A receiver operating characteristic (ROC) curve was constructed to assess the discriminative ability of the percentage change in intraventricular volume and to determine the cutoff point with the best balance between sensitivity and specificity using the Youden index. Bivariate analysis was performed using nonparametric tests. Results: The percentage change in intraventricular volume showed an area under the curve (AUC) of 0.95 (95% CI: 0.85–1.00), indicating a high ability to discriminate between patients with and without clinical complications. A cutoff value of ≥0.9% showed a sensitivity of 90% and a specificity of 100%. Patients with complications exhibited an increase in intraventricular volume (+3.2%; IQR: 2.09–4.17), whereas patients without complications showed a decrease (−6.3%; IQR: −7.4 to −2.0); this difference was statistically significant. Conclusions: The percentage change in intraventricular volume measured using 3D Slicer demonstrated high discriminative ability to differentiate the presence of clinical complications in pediatric patients after hydrocephalus surgery in this series.